ENGINEERING PROPERTIES OF BITUMINOUS MIXTURES CONTAINING HYDROPHILIC AND HYDROPHOBIC AGGREGATES - ZAABA, FADIA DYNI (IRC, 2016)
Mineral aggregate constitute 95% of hot mix asphalt (HMA) by weight. Therefore, it contributes significantly to the characteristics of the bituminous mixtures. For materials of such importance, there is a different between the properties of aggregates used. This project is to determine the engineering properties of the bituminous mixtures containing two types of aggregates which is the hydrophilic and hydrophobic aggregates. Moisture susceptibility in bituminous mixture reduces the strength and durability of the bitumen pavement due to the presence of water. Water disrupts the bond between aggregate and bitumen. Because aggregate comprises 95% of bituminous mixtures, it has a major effect on the performance of mixture. Thus, the choice of right aggregate is important to reduce the presence of water. There are two points that have been identified in stripping: a failure of bonding of the binder to the aggregate (failure of adhesion) and a failure within the binder itself (failure of cohesion).Los Angeles abrasion value, aggregate impact, water absorption capacity and specific gravity tests were conducted to determine the mechanical and physical properties of the aggregates. There are numbers of test has been identified to be used on each type of the aggregates prepared. The test is used to determine the physical and mechanical properties of the aggregates which play a significant role in the bituminous mixtures. In other words, the characteristics of the aggregates will affect the engineering properties of the bituminous mixtures used in the road constructions and also will result in the performance of the road surfaces. The properties of the aggregates will also be compared to the JKR standards and requirements